Role of Yoga and Pranayama in Anxiety: A Review Article - dayal, Shambhu (International Research Journal of Ayurveda & Yoga, 2023)
In India, rates of anxiety are quite high in the general population with women, young adults and the elderly particularly vulnerable. In recent years, Holistic approaches are gaining increasing popularity in the management of psychiatric disorders. Yoga is among the oldest sciences with a holistic approach and hence, has been studied extensively in psychiatry. This increase in popularity is partly due to interest in how this practice, with its aspects of mindfulness and meditation, can reduce anxiety. In yoga, physical postures and breathing exercises improve muscle strength, flexibility, blood circulation and oxygen uptake as well as hormone function. In addition, the relaxation induced by meditation helps to stabilize the autonomic nervous system with a tendency towards parasympathetic dominance. Physiological benefits which follow, help yoga practitioners become more resilient to stressful conditions.